2017
DOI: 10.1017/s135561771700008x
|View full text |Cite
|
Sign up to set email alerts
|

Academic Outcomes in Individuals With Childhood-Onset Epilepsy: Mediating Effects of Working Memory

Abstract: For children with intractable epilepsy, working memory deficits present a significant barrier to the development of academic skills. Working memory interventions may be a helpful adjunct to academic remediation in this population to facilitate academic progress. (JINS, 2017, 23, 594-604).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 45 publications
0
13
0
1
Order By: Relevance
“…As developmental gains would not be expected in the early stages following pediatric surgery, our findings of a stabilization may be a greater reflection of the limited intervals between surgery and follow-up. Considering the mediating effects of domains such as working memory [82] and executive function [83] on academic achievement, our findings in relation to wider cognitive outcomes are promising for academic performance in the years following epilepsy surgery.…”
Section: Discussionmentioning
confidence: 83%
“…As developmental gains would not be expected in the early stages following pediatric surgery, our findings of a stabilization may be a greater reflection of the limited intervals between surgery and follow-up. Considering the mediating effects of domains such as working memory [82] and executive function [83] on academic achievement, our findings in relation to wider cognitive outcomes are promising for academic performance in the years following epilepsy surgery.…”
Section: Discussionmentioning
confidence: 83%
“…Embora tão oportunos na epilepsia, os anticonvulsantes não têm efeitos terapêuticos na narcolepsia e levam a custos desnecessários e efeitos colaterais, como o ganho de peso, que já compõem a morbidade da própria doença (Poli et al, 2013). Vale ressaltar, ainda, que crises epilépticas de ausência, que provocam no paciente episódios de olhar vago e distanciamento do seu arredor, figuram como a principal e muitas vezes única manifestação de várias síndromes epilépticas, como a epilepsia generalizada idiopática, e também podem cursar com alterações arquiteturais do sono e queda do rendimento escolar, devendo ser pensadas como diagnóstico diferencial (Dinopoulos et al, 2018;Danguecan & Smith, 2017).…”
Section: Discussionunclassified
“…Focal neurocognitive deficits, such as declarative and working memory disorders, might explain the impact on learning and academic skills. 37 These deficits typically do not affect daily living independence or the ability to obtain a regular school degree. 38 Similar to the findings of Reinholdson et al, 18 we observed no effect of seizure freedom on academic achievement.…”
Section: Academic Attainmentmentioning
confidence: 99%